2020
DOI: 10.29062/edu.v4i1.74
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Online Learning toward Students’ Academic Performance on Business Correspondence Course

Abstract: Covid-19 pandemic becomes global issue that gives global impact in all sectors especially in educational one. The Minister of Education and Culture of Indonesia make a policy in which all education sectors are shifted from face-to-face learning into online learning. This policy is well-responded by one of private universities in Lampung. The researcher conducted a research to response this policy. The objective of this study is identify the impact of online learning toward students’ academic performance on Bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 11 publications
1
43
0
1
Order By: Relevance
“…There are several related studies have conducted previously about online learning and students' motivation. Mandasari (2020) in her study about the impact of online learning toward students' academic performance on Business Correspondence course found that online learning has positive impact on students' academic performance in term of learning motivation, learning achievement and learning engagement. In addition, it was also found that participants showed that conducting online learning is relevant during pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…There are several related studies have conducted previously about online learning and students' motivation. Mandasari (2020) in her study about the impact of online learning toward students' academic performance on Business Correspondence course found that online learning has positive impact on students' academic performance in term of learning motivation, learning achievement and learning engagement. In addition, it was also found that participants showed that conducting online learning is relevant during pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Te comprehensive evaluation of class students' academic performance of college is an important element of education evaluation. Te comprehensive evaluation of students' academic performance is an important element of educational evaluation [1][2][3]. It is also an important indicator for the evaluation of merit and priority and the awarding of various scholarships.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pandemic breakout forced schools to adopt a new learning modality, many studies have already investigated the effects of online learning on students' academic performance (Arcinas, 2022, Han & Ellis, 2021Mandasari, 2020;Oducado & Estoque, 2021, Rad et al, 2022. However, few studies consider the environmental factors behind students' virtual learning, such as light, noise, and temperature, as significant contributors to students' intellectual development.…”
Section: Introductionmentioning
confidence: 99%